No prognostic value of IDH1 mutations in a series of 100 WHO grade II astrocytomas - Ahmadi, Rezvan; Becker, Natalia; Dictus, Christine; Herold-Mende, Christel; Unterberg, Andreas; Capper, David; Deimling, Andreas von; Wick, Wolfgang (Journal of neuro-oncology, 2012)
Mutations in the gene encoding isocitrate dehydrogenase 1 (IDH1) have been identified in approximately 70-80 % of astrocytomas and oligodendrogliomas of WHO grades II and III, and in secondary glioblastomas. In addition, a low incidence of IDH2 mutations has been detected in these tumors, and the occurence of IDH1 and IDH2 mutations is mutually exclusive. For patients with anaplastic gliomas and glioblastomas with IDH1 mutations, overall survival was significantly longer than for patients with wild-type tumours. However, the prognostic value of IDH1 in low-grade gliomas remains ambiguous. IDH1 codon 132 and IDH2 codon 172 mutation status were determined by direct sequencing for a retrospective series of 100 patients with histologically diagnosed Astrocytomas WHO Grad II (A II), and investigated for association with patient outcome. For the patient cohort analysed, median progression-free survival (PFS) was 44.6 months (95 %-CI 1.0-267.0), time to progression (median time to malignant progression (TtMP) was 74.9 months (95 %-CI 1.6-236.2), and median overall survival (OS) was 81.4 months (95 %-CI 5.5-274.8). IDH1 mutations were identified in 79 % of the patients. IDH2 mutations were not observed. Univariate and multivariate analysis revealed no association between IDH1 mutation status and PFS, TtMP, and OS. Furthermore, there were no significant differences regarding PFS, TtMP, and OS between patients with and without IDH1 mutations who did not receive adjuvant treatment. The prognostic value of IDH1 mutations in low-grade astrocytomas is rather low compared with that in high-grade gliomas.
Gesehen am 09.01.2019